Periprosthetic fractures of the femur: our experience - Valentini, Roberto; Martino, Marcellino; De Fabrizio, Giovanni; Fancellu, Giovanni (Acta Biomedica Atenei Parmensis, 2014)
A frequent problem in Orthopedic surgery is represented by periprosthetic fractures in Total Hip Arthroplasty (THA). The incidence of this pathology has interested 1,5% in primary THA and till 6-8% in revision prosthesis during last 10 years. About this contest, the authors performed a study on 24 patients (6 males; 18 females) surgically treated for periprosthetic femoral fracture at the Orthopedic and Traumatologic Clinic, University of Trieste, Italy, in the period from January 2006 to December 2011.  Periprosthetic fractures were classified following guide-lines of the Vancouver Classification System. Even the choice of treatment was based on Vancouver Classification System, on patient clinical conditions and patients age.